Polyurethane coated with polyvinylpyrrolidones via triazole links for enhanced surface fouling resistance. Issue 4 (20th August 2021) - Wen, Xin; Almousa, Rashed; Na, Sungsoo; Anderson, Gregory G.; Xie, Dong
Abstract: Surfaces with hydrophilic and antimicrobial properties are very attractive for cardiovascular device‐associated applications. The aim of this study was to prepare and coat a hydrophilic polymer containing a functional group capable of forming triazole functionality onto the surface of polyurethane (PU). The modified surfaces were assessed with cell adhesion, bacterial adhesion and bacterial viability. Mouse fibroblast cells (NIH‐3T3) and three bacterial species were used for assessment. The results showed that the modified surface not only exhibited a significant reduction in cell adhesion with a 25%–59% decrease to mouse fibroblast but also showed a significant reduction in bacterial attachment with 26%–67%, 24%–61% and 23%–57% decrease to Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa, respectively, as compared with original PU. Furthermore, the polymer‐modified surface exhibited a significant antibacterial function by inhibiting bacterial growth with reduction of 49%–84%, 44%–79% and 53%–79% to S . aureus, E . coli and P . aeruginosa, respectively, as compared with original PU. These results indicate that covalent polymer attachment enhanced the antibacterial and antifouling properties of the PU surface.